2003
DOI: 10.1073/pnas.1332709100
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant lymphocytic choriomeningitis virus expressing vesicular stomatitis virus glycoprotein

Abstract: T he prototypic arenavirus lymphocytic choriomeningitis virus (LCMV) is an important model to study both acute and persistent viral infection, as well as virus-host balance (1) and associated disease (2). Important concepts of immunology (3) and viral pathogenesis (4) have been developed by using the LCMV model. In addition, LCMV provides an excellent system to study basic aspects of the molecular and cell biology of clinically important human pathogens, including Lassa fever virus (LFV) and other arenaviruses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 28 publications
4
97
0
1
Order By: Relevance
“…Neither LCMV nor rVSV/LCMV-GP induced detectable VSV-IND nAb's because they lacked INDG. All VSV-neutralizing serum samples neutralized rLCMV/INDG in vitro ( Figure 2C), confirming that rLCMV/INDG infectivity was INDG-mediated (18). But neither of the sera collected during this experiment exhibited neutralizing activity against rVSV/LCMV-GP ( Figure 2B) or LCMV-ARM (Figure 2D).…”
Section: Introductionmentioning
confidence: 51%
See 3 more Smart Citations
“…Neither LCMV nor rVSV/LCMV-GP induced detectable VSV-IND nAb's because they lacked INDG. All VSV-neutralizing serum samples neutralized rLCMV/INDG in vitro ( Figure 2C), confirming that rLCMV/INDG infectivity was INDG-mediated (18). But neither of the sera collected during this experiment exhibited neutralizing activity against rVSV/LCMV-GP ( Figure 2B) or LCMV-ARM (Figure 2D).…”
Section: Introductionmentioning
confidence: 51%
“…Infection of mice with either of the two recombinant or WT viruses revealed a critical role for the GP but not for the viral backbone in determining nAb kinetics. ly reported that propagation and peak titers of rLCMV/INDG are reduced when compared with LCMV-ARM (18). In vitro growth curves revealed that rVSV/LCMV-GP was similarly attenuated when compared with VSV-IND ( Figure 1D).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…GPC is transcribed as a single protein and then is posttranslationally cleaved by a host protease S1P to form GP1 and GP2, the virion surface glycoproteins (Beyer et al, 2003;Pinschewer et al, 2003). GP1 mediates attachment of the virus to its cellular target and subsequent receptor-mediated endocytosis (Pasqual et al, 2011).…”
Section: Viral Proteinsmentioning
confidence: 99%